2018
DOI: 10.1080/14656566.2018.1428560
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of endothelial function by pitavastatin: a meta-analysis

Abstract: This meta-analysis of all available clinical trials revealed a significant increase of FMD induced by pitavastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Therefore, the consequence of impaired endothelium-mediated dilatation in the resistance vessels would be the elevation of SVR. Twelve month treatment with statins improved flow-mediated dilatation in the brachial artery [25], while a meta-analysis reported increased flow-mediated dilatation following treatment with pitavastatin [26].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the consequence of impaired endothelium-mediated dilatation in the resistance vessels would be the elevation of SVR. Twelve month treatment with statins improved flow-mediated dilatation in the brachial artery [25], while a meta-analysis reported increased flow-mediated dilatation following treatment with pitavastatin [26].…”
Section: Discussionmentioning
confidence: 98%
“…As the deleterious effect of LDL-C on endothelial dysfunction can be reversed by statins, this provides a potential explanation for the beneficial effects of these agents on BP [20,[24][25][26]. Experimental evidence suggests that LDL-C can increase the angiotensin II type 1 receptor density in the arterial wall [15,17], while statin treatment in vivo can reduce the vasoconstrictor responses elicited by angiotensin II in isolated human internal thoracic artery segments in vitro [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as well as immunomodulation, COVID-19 treatment should also target reduction of inflammation. In this context, statins have been consistently reported to exert immunomodulatory and anti-inflammatory properties [20][21][22][23][24][25][26][27][28][29][30]. Also, it was previously suggested that statins could enhance host defence and suppress inflammation, thus representing a practical and inexpensive adjunctive or alternative host-directed treatment for infections by viruses, fungi, protozoa, and bacteria [31].…”
mentioning
confidence: 99%
“…FMD has been shown to be impaired in patients with traditional coronary risk factors, including hypertension, dyslipidemia, diabetes mellitus, and smoking, and it has been considered to be a cause of atherosclerosis [14]. Statins improve endothelial function as assessed by FMD [15,16]. In addition, hypertriglyceridemia is independently associated with endothelial dysfunction as assessed by FMD in patients with CHD during statin therapy [17].…”
Section: Introductionmentioning
confidence: 99%